2018
DOI: 10.3892/ol.2018.7887
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma cells surviving doxorubicin treatment exhibit increased migratory potential and resistance to doxorubicin re-treatment in�vitro

Abstract: Abstract. Transarterial chemoembolization (TACE) is an established therapeutic approach for the treatment of hepatocellular carcinoma (HCC). Although patients who undergo TACE may have prolonged survival, there are indications that the malignancy of residual HCC tissue can increase subsequent to the procedure. Although hypoxia, which occurs during TACE due to ischemia, is known to contribute to angiogenesis, little is known with regard to the undesirable effects of chemotherapeutic agents on residual HCC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Drug resistance arises commonly in cancers and leads to the failure of chemotherapy in nearly all advanced patients 54 , 55 . HCC is one of the most malignant cancer types yet displayed rather low chemosensitivity 56 , 57 . In order to finally overcome the chemoresistance and maximize the chemotherapy benefits in HCC, many efforts should be made toward a better understanding of the underlying mechanism 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance arises commonly in cancers and leads to the failure of chemotherapy in nearly all advanced patients 54 , 55 . HCC is one of the most malignant cancer types yet displayed rather low chemosensitivity 56 , 57 . In order to finally overcome the chemoresistance and maximize the chemotherapy benefits in HCC, many efforts should be made toward a better understanding of the underlying mechanism 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 41 of 51 patients (80%) presented TACE failure/refractoriness, and the high number of TACE treatments (median of 3) before initiation of lenvatinib may have caused the high distribution of heterogeneously enhanced target nodules in this cohort. Previously, other researchers reported that TACE treatment induced a more malignant phenotype of HCC, including poorly-differentiated histology and CK19 expression indicative of the more aggressive biliary phenotype [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been described to contribute to the acquired resistance to DOX [39]. Firstly, an upregulation of multidrug resistance efflux pumps could create a reduction in nuclear drug accumulation [40]. Unfortunately, the biomarkers analyzed with the oncology panel did not represent proteins for drug response, which could be why there were no noticeable differences in hierarchical clustering on treatment levels.…”
Section: Discussionmentioning
confidence: 99%